Characterization of Potential Virulence Factors of Vibrio mimicus Isolated from Fishery Products and Water - M. F. Hernández-Robles; I. Natividad-Bonifacio; A. K. Álvarez-Contreras; J. J. Tercero-Alburo; E. I. Quiñones-Ramírez; C. Vázquez-Salinas (International Journal of Microbiology)
Vibrio mimicus is a Gram-negative bacterium that is closely related to V. cholerae and causes gastroenteritis in humans due to contaminated fish consumption and seafood. This bacterium was isolated and identified from 238 analyzed samples of sea water, oysters, and fish. Twenty strains were identified as V. mimicus according to amplification of the vmhA gene, which is useful as a marker of identification of the species. The production of lipases, proteases, and nucleases was detected; 45% of the strains were able to produce thermonucleases and 40% were capable of producing hydroxamate-type siderophores, and the fragment of the iuT gene was amplified in all of the V. mimicus strains. Seventy-five percent of V. mimicus strains showed cytopathic effect on Chinese hamster ovary (CHO) cells and destruction of the monolayer, and 100% of the strains were adherent on the HEp-2 cell line with an aggregative adherence pattern. The presence of virulence factors in V. mimicus strains obtained from fishery products suggests that another member of the Vibrio genus could represent a risk to the consumer due to production of different metabolites that allows it to subsist in the host.